Firing mechanism and benefit evaluation of high-strength fired water permeable brick containing vanadium-titanium iron ore tailings - Bao, Pingju; Jing, Jianlin; Qi, Yang; Ma, Jintao; Ping, Haoyan; Wang, Changlong; Liu, Zhibing; Zheng, Yongchao; Zhai, Yuxin; Liu, Feng (Frontiers in Earth Science, 2023)
The vanadium-titanium iron ore tailings (VTIOTs) has a significant amount of discharge, and serious pollution, which makes it difficult to use directly as a resources. High-strength fired water permeable brick (HSFWPB) was prepared using VTIOTs as the main raw material. The orthogonal test, X-ray diffraction analysis (XRD), scanning electron microscope (SEM) and energy dispersive spectrometry (EDS) were obtained to study the basic properties and firing mechanism of HSFWPB containing VTIOTs, and an economic benefit evaluation was conducted on the project investment of HSFWPB containing VTIOTs. The results show that when the content of VTIOTs in HSFWPB is 78%, the firing temperature (FT) is 1080 OC and the holding time is 120 min, the compressive strength and permeability coefficient of the fired product reach 65.7 MPa and 0.061 cmˑs-1, respectively, which meet the requirements of Cc60 grade products in Water permeable brick (JC/T 945—2005). The products of HSFWPB containing VTIOTs after firing are diopside (CaMgSi2O6) and augite (Ca(Mg,Fe,Al)(Si,Al)2O6), with the increase of FT and the extension of HT, the low melting point elements of P, Na, K dissolve out, and the content of Fe and Al in the firing products increases, most of Ca2+ in diopside is replaced by Fe3+, so that augite becomes the main crystal phase. With the increase of FT, the pores in the fired products are changed from: closed pores with different sizes→ connected pores with irregular diameters→ irregular collapse pores→ small and uniform circular pores, it provides a guarantee for the permeability of HSFWPB containing VTIOTs. The full investment payback period of project of HSFWPB containing VTIOTs is 1.77 years. When the production reaches 48.585% of the design output, it reaches a breakeven point, and the project has strong risk resistance ability. The research has improved the utilization rate of VTIOTs and provided a new approach for the large-scale application of VTIOTs.